Gustave Bertrand: the Cooperation of British Intelligence with an Officer in Vichy France - (:unkn) unknown (My University, 2022)
This paper investigates the little-known yet crucial part that cooperation with Frenchcryptanalysts played in the remarkable British success in cracking Enigma codes during World War Two. On the French side, the central figure of this alliance was the head of the French army codebreaking unit, Gustave Bertrand. Shortly before the war, he had put British and Polish cryptanalysts in contact with each other, and this became instrumental in allowing the British to decode Enigma messages. After the fall of France in 1940, Bertrand chose to remain in France and, with the support of some leading Vichy officials, kept on working on German codes and cooperated with the British, on a clandestine basis. This entailed huge risks for the two partners. The Allied landing in North Africa all but put an end to this alliance, although a few exchanges did take place after that date. This cooperation paved the way for the massive expansion of the British codebreaking centre, which became a world leader in the field.
Keywords: African Research